La celebración del Sacramento del Matrimonio en la tradición hispana - Grenesche , Juan Miguel Ferrer (Verbum Vitae, 2025)
This paper aims to offer a diachronic view of the celebration of Marriage in the territory of ancient Roman Hispania, coinciding with the Iberian Peninsula. From pre-Roman times to the present day, focusing, in particular, on the evolution of these rites from Christianization to the rituals in force today. Emphasizing the origin, formation/codification and survival of the tradition of what is now known as the Hispano-Mozarabic Rite. As can be seen from the chapter titles of this work, a chronological analysis of the development of the institution of marriage in the territory of the Iberian Peninsula has been followed. At the same time, whenever possible, some synchronous comparisons have been made between the Roman rite and the Hispano-Mozarabic rite. The methodology combines reference to specialized studies, with regard to the tradition of marriage in the peoples of pre-Roman and Roman Hispania; and for the entire Christian period, direct recourse to successive liturgical sources, without forgetting reference to some specialized studies on this period. Particular note is taken of the importance of the Roman-pagan rites and the process of Christian inculturation involving them and their maintenance, even within the Roman liturgy, to the present day. Thus confirmed is the conviction implied in these rites and texts concerning the origin of matrimony in the creation and its continuity and perfection when Christ raised it to the status of a sacrament, which appears to be deeply grounded in theology and involving the ecclesial community as a whole. At the same time, the insistence on the acknowledgement of common dignity between husband and wife within marriage stands out.